The effect of hearing loss configuration on cochlear implantation uptake rates: an Australian experience. (30th October 2020) - Sucher, Cathy M.; Eikelboom, Robert H.; Stegeman, Inge; Jayakody, Dona M. P.; Atlas, Marcus D.
Abstract: Objective: Recent changes to cochlear implant (CI) candidacy criteria have led to the inclusion of candidates with greater levels of hearing in the contralateral and/or implanted ear. This study assessed the impact of various hearing loss configurations on CI uptake rates (those assessed as eligible for CI, who proceed to CI). Design: Retrospective cohort study. Study sample: Post-lingually deaf adult CI candidates ( n  = 619) seen at a Western Australian cochlear implant clinic. Results: An overall CI uptake rate of 44% was observed. Hearing loss configuration significantly impacted uptake rates. Uptake rates of 62% for symmetrical hearing loss, 48% for asymmetrical hearing loss (four-frequency average hearing loss (4FAHL) asymmetry ≤60 dB), 25% for highly asymmetrical hearing loss (4FAHL asymmetry >60 dB), 38% for hearing losses eligible for electric-acoustic stimulation, and 22% for individuals with single-sided hearing loss were observed. Hearing loss configuration and age were both significant factors in relation to CI uptake although the impact of age was limited. Conclusion: CI clinics who apply or are considering applying expanded CI candidacy criteria within their practice should be aware that candidates with greater levels of residual hearing in at least the contralateral ear are less likely to proceed to CI.